2018
DOI: 10.3390/mi9080384
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Deformability and Velocity of Healthy and Artificially Impaired Red Blood Cells in Narrow Polydimethylsiloxane (PDMS) Microchannels

Abstract: Malaria is one of the leading causes of death in underdeveloped regions. Thus, the development of rapid, efficient, and competitive diagnostic techniques is essential. This work reports a study of the deformability and velocity assessment of healthy and artificially impaired red blood cells (RBCs), with the purpose of potentially mimicking malaria effects, in narrow polydimethylsiloxane microchannels. To obtain impaired RBCs, their properties were modified by adding, to the RBCs, different concentrations of gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…As shown in Figure 1a, a multi-layer mold was designed to improve precision and repeatability. The stainless steel template had high stiffness and ccould be reused without wear, compared with conventional PDMS or SU-8 soft-lithography [29,30]. Chemical etching is a common method to pattern stainless steel with high-resolution, which determines the shape and height of micromachines [31].…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Figure 1a, a multi-layer mold was designed to improve precision and repeatability. The stainless steel template had high stiffness and ccould be reused without wear, compared with conventional PDMS or SU-8 soft-lithography [29,30]. Chemical etching is a common method to pattern stainless steel with high-resolution, which determines the shape and height of micromachines [31].…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, the deformability of single RBC was quantified with several quantifiers such as the deformability index (DI), cell margination, transit time, individual RBC velocity, and cell lysis. By referring to the recent work conducted by Catarino et al [ 37 ], the deformability index (DI) was found to be proportional to the RBC velocity for various degrees of RBCs, by measuring the RBC velocity and the deformed shape of RBCs. From this result, RBC velocity travelled in the microfluidic channel varied depending on the RBC deformability.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of RBCs in plasma and their deformability, in healthy conditions, plays an important role to define blood as a non-Newtonian fluid [1]. Some diseases, such as sickle-cell anemia, malaria, diabetes, polycythemia, cancer, heart disease are responsible to change the rheological and flow properties of the blood [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%